Avifauna of Noakhali Science and Technology University premises and adjacent areas - Mahmud, Humayra; Sultana, Sadia; Akter, Nasrin; Talukder, Rasel (Journal of Bangladesh Academy of Sciences, 2024)
A study was carried out from September 2021 to September 2023 to estimate the diversity, seasonal variation, and relative abundance of avifauna of Noakhali Science and Technology University and its adjacent areas. One hundred fourteen bird species were recorded from the study site belonging to 18 different orders. Of these, one species, Grey-headed Fish Eagle Haliaeetus ichthyaetus, has been rated globally as Near Threatened (BirdLife International 2021). The distribution of birds among habitat types was significantly different (f=7.153, p<0.05, df=2). The walking trail was inhabited with the highest species diversity (H'= 3.45) with the highest evenness (J= 0.84), while grassland was recorded with the lowest species diversity (H'= 2.69) but had almost similar evenness index (J= 0.84); it could have a relation to the food availability. Considering the richness of bird species, the existing habitats will be restored. J. Bangladesh Acad. Sci. 48(2); 237-250: December 2024